Management of Hallux Valgus in adults by Chveron Corrective Osteotomy - Waqas Ahmed, Zafar Ali, Muhammad Khalid Syed, Syed Imran Haider, Muhammad Mazhar Rafiq, Tauseef Ahmad Baluch (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Hallux valgus is a complex deformity and although not common but difficult to treat .It started from first row and then involve the entire foot. There are many surgical techniques to treat this problem. Both soft tissue procedures and bony osteotomies are mentioned in literatures but still there is no any gold standard. We used soft tissues procedure and cheveron osteotomy for treatment. Coughlin classification was used to assess the outcome Aim: To assess the outcome of cheveron corrective osteotomy to treat hallux valgus deformity in adult by using Coughlin’s classification. Methods: We operated 15 adults patients with hallus valgus in Mayo hospital Lahore between 1-6-19 to 31-12-19 .Both soft tissues and bony procedure were done, Coughlin’s classification used to assess the pre operative and post operative deformity. Results: From total 15 patients 5 were male (27.3%) and 10 were female (72.7%). The mean age was 31.63 years (SD =1,689), ranging from 20 to 50 years old. Right side was involved in 4 (26.66%) patients foot affected, left side was involved in 5(33.33%) patients and both sides were involved in 6(40%) patients. Postoperatively, 12 patients (72.7%) showed the first ray angles within acceptable values. All patients had cosmetic correction and 13 patients (90.9%) had relief of pain and suitability for footwear. Conclusion: Chevron osteotomy is effective safe and treatment of choice in adults . Key words: Soft tissues, Hallux Valgus, Chevron osteotomy